2020
DOI: 10.1017/s000711452000481x
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated pomegranate peel extract induces mitochondrial complex IV activity and prevents mitochondrial cristae alteration in brown adipose tissue in mice fed on a high-fat diet

Abstract: Pomegranate peel is an agro-industrial residue obtained after fruit processing with high total polyphenol (TP) content, making it an attractive by-product for its reuse. Pomegranate peel extract (PPE) and its bioactive compounds have shown positive effects on obesity models. Effects on favouring mitochondrial biogenesis and function have also been described. However, once phenolic compounds are extracted, their stability can be affected by diverse factors. Microencapsulation could improve PPE stability, allowi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
3
8
0
3
Order By: Relevance
“…In general, pomegranate peel extract has been confirmed as a highly valuable source of bioactive compounds that can be used to improve the functional characteristics of food when used in ethanolic form [ 76 ]. The mix of flavonoids, polyphenols, and other active ingredients found in pomegranate peel have been published previously, confirming that the antioxidant activity in the pomegranate can be attributed mainly to its polyphenol, quercetin, and rutin contents [ 77 ].…”
Section: Discussionsupporting
confidence: 67%
“…In general, pomegranate peel extract has been confirmed as a highly valuable source of bioactive compounds that can be used to improve the functional characteristics of food when used in ethanolic form [ 76 ]. The mix of flavonoids, polyphenols, and other active ingredients found in pomegranate peel have been published previously, confirming that the antioxidant activity in the pomegranate can be attributed mainly to its polyphenol, quercetin, and rutin contents [ 77 ].…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have suggested that the alignment of mitochondrial cristae and mitochondrial cristae density are a dynamic process associated with OXPHOS activity 30–32 . Here, our results show that glucose consumption after fasting reduces mitochondrial cristae alignment, length and number, as well as reduces mitochondria‐ER interaction, Mfn2 protein and CV‐ATP5A levels.…”
Section: Discussionsupporting
confidence: 71%
“…28,29 Previous studies have suggested that the alignment of mitochondrial cristae and mitochondrial cristae density are a dynamic process associated with OXPHOS activity. [30][31][32] Here, our results show that glucose consumption after fasting reduces mitochondrial cristae alignment, length and number, as well as reduces mitochondria-ER interaction, Mfn2 protein and CV-ATP5A levels. Once again, similar observations were previously made in the liver, as the postprandial state was associated with reduced mitochondria cristae length through a Mfn2 and Opa1dependent mechanism.…”
Section: Discussionsupporting
confidence: 55%
“…MIC60 is the core component of the mitochondrial contact site and cristae organizing system and interacts with several inner and OMM proteins to maintain inner mitochondrial membrane morphology and density 25 . It has been suggested that the typical architecture of cristae provides a specific microenvironment that enhances the catalytic capacity of the OXPHOS system 26 . It was previously shown in HeLa cells that MIC60 knockout, decreases the activity of mitochondrial OXPHOS complexes I, III and IV 27 .…”
Section: Discussionmentioning
confidence: 99%